2013
DOI: 10.5152/eajm.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Anatomic Variations of the Paranasal Sinuses and Ethmoid Roof Using Computed Tomography

Abstract: Using the Keros classification for LLCP height, higher rates of Keros Type I were found in other studies than in our study. The most frequent classification was Keros Type II. The paranasal sinus variations in each patient should be carefully evaluated. The data obtained from these evaluations can prevent probable complications by informing rhinologists performing endoscopic sinus surgery about preoperative and intraoperative processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
42
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
15
42
1
9
Order By: Relevance
“…Thus basal lamella of the middle nasal concha represents the surgical posterior limit for an anterior ethmoidectomy. Anatomic variations of ethmoid cells have been reported [7][8][9] whereas anterior, middle and posterior ethmoid cells communications with each other through unusual hole noted in this study such congenital malformation of bony orbit have not been reported in the modern medical literature. Such variable bony orbit anatomy helps in understanding the pathophysiology and spread of sinus disease, as well as performing the most complete ethmoid surgery with the least surgical complications.…”
Section: Discussionmentioning
confidence: 47%
“…Thus basal lamella of the middle nasal concha represents the surgical posterior limit for an anterior ethmoidectomy. Anatomic variations of ethmoid cells have been reported [7][8][9] whereas anterior, middle and posterior ethmoid cells communications with each other through unusual hole noted in this study such congenital malformation of bony orbit have not been reported in the modern medical literature. Such variable bony orbit anatomy helps in understanding the pathophysiology and spread of sinus disease, as well as performing the most complete ethmoid surgery with the least surgical complications.…”
Section: Discussionmentioning
confidence: 47%
“…Our results are comparable to those found out by Perez-Pinas et al [3] (24.5%), Basi et al [12] (21%) and Jones et al [13] (20%). Higher frequencies were found out by Ka-Planoglu et al [1] (30.4%), Keast et al [14] (29%), Tonai et al [15] (28%), and Azila et al [16] (40.8%). However Bolger et al [17] reported a low frequency of 15.7%.…”
Section: Discussionmentioning
confidence: 78%
“…Blaugrund et al [4] found out a frequency of 20%. High frequencies were found out by Perez-Pinas et al [3] (55%), Kaplanoglu et al [1] (82%), Danese et al [5] (52%), and Earwaker et al [2] (44%). The low frequency of our study can be explained by the choice of our selection criteria on the deviations of the nasal septum.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations